Enriching Students’ Vocabularies through Pictionary Games in Small Group Discussions - Yuliani, Novi Dwi; Kamalia, Niska; Ulfah, Lisnani (English Teaching and Linguistics Journal (ETLiJ), 2024)
The intention of this experimental research is to investigate the impact of small group discussion techniques using pictionary game on students’ vocabulary achievement targeting 7th grade students of MTsN 1 Banjar. The methodology of the study is designed to be a quantitative conducted by applying the pre-test and post-test. A total of 62 7th graders were the subjects of the study. Samples were taken using intentional sampling techniques, involved two classes with 31 students each. These classes are assigned to experimental and control classes. Prior to starting treatment, a pre-test was administered to check the student's basic vocabulary comprehension. Data collection were from the test applied before and after the experimental treatment. After calculation, considering the value of 30.38, which is greater than 0, it can be stated that the small group discussion technique is effective in learning vocabulary. The t-observation value (up to 30.38) is higher than the t-table (table = 1.699), demonstrating whether the Small Group Discussion is significantly effective for enriching vocabularies compared to using other techniques that usually implemented by the teacher at MTsN 1 Banjar, South Kalimantan.